(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In the first half of the 18th century, at the time of the accession of Kazakhstan to Russia, there were only a few small towns in its steppe spaces. Therefore, among the scholars and travelers of those times, there was an idea of ​​Kazakhstan as a country of endless steppes in which “wild nomads” live, overwhelmed with a passion for the destruction of everything that hinders free movement. Later, the Russian archeologist, the researcher of the ancient Khorezm, S.P. Tolstov, refuting this opinion, comes to the conclusion that “it would be a mistake to see in the urban civilization only the product of the development of only agricultural oases”